Thyroid Sarcomatoid Carcinoma – Showing Positive Scan on 18F FDG PET-CT - Reza, Sharmin; Ferdousi Begum, Shamim Momtaz; Begum, Fatima (Bangladesh Journal of Nuclear Medicine, 2022)
A 47 years old woman presented with a longstanding multinodular goiter (MNG) for 10 years with history of Fine needle aspiration cytology (FNAC) proven nodular goiter at her initial diagnostic workup and no further follow up. Recently, she noticed rapidly growing swelling of neck with occasional shortness of breath and pain within the mass. A thyroid scintigraphy at the National Institute of nuclear Medicine & Allied Sciences (NINMAS) revealed multinodular goiter with a dominant cold nodule in left lobe. Patient underwent total thyroidectomy with left sided neck dissection and clearance of cervical lymph nodes. Histopathology reported metastatic papillary carcinoma with spindle cell differentiation. Immunohistochemistry findings were suggestive of sarcomatoid carcinoma presumably with a spindle cell differentiation at metastatic site. Post thyroidectomy imaging with18F-fluorodeoxyglucose Positron Emission Tomography-Computed Tomography (18F-FDG PET-CT) revealed irregular lobulated soft tissue area with intense FDG avidity in neck region. Diagnostic whole body scan (WBS) with 131I showed no uptake of radioiodine anywhere in the body. Patient received chemotherapy but survived only two months after that. Bangladesh J. Nuclear Med. 23(1&2): 59-62, 2020